2014
DOI: 10.1212/wnl.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Brain functional connectivity network breakdown and restoration in blindness

Abstract: Vision loss in the blind is caused not only by primary tissue damage but also by a breakdown of synchronization in brain networks. Because visual field improvements are associated with resynchronization of alpha band coherence, brain connectivity is a key component in partial blindness and in restoration of vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 41 publications
3
105
0
10
Order By: Relevance
“…We have recently shown that in patients with vision loss caused by pre-chiasmatic lesions spatial patterns of functional connectivity are impaired (Bola et al, 2014). Specifically, we observed that vision loss was associated with impaired synchronization in the high-alpha band .…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…We have recently shown that in patients with vision loss caused by pre-chiasmatic lesions spatial patterns of functional connectivity are impaired (Bola et al, 2014). Specifically, we observed that vision loss was associated with impaired synchronization in the high-alpha band .…”
Section: Introductionmentioning
confidence: 73%
“…retinal and/or optic-nerve) visual system damage and 13 control subjects that had no neurological dysfunctions. Their data were already analyzed by different methods and published elsewhere (Bola et al, 2014).…”
Section: Subjectsmentioning
confidence: 99%
“…Therefore, it is speculated that vision loss in the blind is caused not only by primary tissue damage but also by breakdown of synchronization in brain networks. 48 In addition, transorbital ES in patients with optic nerve damage showed significant increases in detection ability, visual field, and visual acuity. 49e52 All three published studies on the use of transpalpebral ES were performed in patients with AMD (Table 3).…”
Section: Transorbital and Transpalpebral Es In Clinical Trialsmentioning
confidence: 96%
“…There are also ongoing clinical trials about this therapy in non-arteritic anterior ischemic optic neuropathy (NA_AION) and traumatic optic neuropathy (TON) [4]. Another study performed for 10 days using lid electrodes and transorbital stimulation instead of transcorneal impulses in optic neuropathies resulted in an average of 25% improvement in VF defects [5]. In this study, alternating current therapy was applied through the eyelids.…”
Section: Introductionmentioning
confidence: 99%